Local Wisdom-Based Avatar Video With a Historical and Social Approach to 21st Century Language Learning - Ilmi Solihat; Etika Khaerunnisa; Sholeh Hidayat; Luluk Asmawati (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2026)
This study is grounded in the limited integration of digital technology and local wisdom in language learning, where instructional practices remain predominantly traditional and insufficiently contextualized within cultural and social dimensions. This study aims to analyze and synthesize the development of local wisdom–based avatar videos using historical and social approaches to support 21st century educational language learning. The study employed a Systematic Literature Review design. Data were collected from articles indexed in Google Scholar, Scopus, ScienceDirect, and ERIC, focusing on publications from the last five years. Article selection followed the PRISMA 2020 protocol, and the data were analyzed using thematic analysis to identify recurring conceptual patterns and pedagogical implications. The findings reveal that avatar based videos integrated with local wisdom enhance not only linguistic competence but also socio cultural understanding and learner identity formation. The historical approach deepens students’ awareness of language evolution and cultural heritage, while the social approach strengthens contextual communication skills and intercultural sensitivity. The study concludes that integrating avatar technology with historical and social perspectives establishes a culturally responsive digital language learning framework. The implications suggest that educators and instructional designers can adopt culturally grounded avatar media to design more contextual, identity oriented, and socially meaningful language learning experiences in 21st century educational.